(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
This paper delves into the dynamic relationship between imaginary and technology in the era of Artificial Intelligence, illustrating how AI’s technological imaginary is not an independent entity but rather a product of the creative process inherent in the social imaginary. Additionally, it explores how the symbolic structures of socio-cultural imaginary contribute to shaping the imaginary realms of AI. The widespread integration of generative AI in fashion has introduced visual AI, offering new avenues for creative expression while challenging the construction of the sector’s imaginary landscape (Banerjee et al. 2022). This prompts critical inquiries: to which extent fashion narratives have become the nourishment of AI? What innovative narrations does AI introduce? How is AI influencing traditional perceptions of the body and beauty? Comparing 882 covers from Vogue Italia Digital Archive (1964-2024) with visuals from the AI-produced fashion magazine Copy (August 2023 onwards), this research analyzes representations and narratives to determine if AI perpetuates or subverts beauty and gender stereotypes, and how the normativity of fashion influences AI’s visual output.